Phytochemical screening and anti-cancer effect of Clinacanthus nutans extract towards cervical cancer cell line, HeLa - Yee, Lim Wei (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Nowadays many researches are focusing on the discovery of new therapeutic substance of natural origin for the treatment of cancer based on its cytoxicity to human cells. Clinacanthus nutans (C.nutans) or locally known as Belalai Gajah in Malaysia have been used in Thailand as a folk medicine for the Herpes virus infection. Recently C.nutans had become popular folk medicine in the treatment of cancer around Malaysia. In the present study, we aim to examine anti-cancer activities of C.nutans extracts for the treatment of cancer in vitro. Aqueous and methanol crude extracts were extracted from the leaves of C.nutans and phytochemical screening was performed to study the plant secondary metabolites. The cytotoxic activity of both crude extracts were investigated in vitro against human cervical cancer cell lines, HeLa by using MTT assay. The mode of cell death induced by the crude extracts of C.nutans was examined by Hoechst 33258 stain. The secondary metabolism constituents in aqueous crude extract are terpenoids and flavonoids, whereas methanol crude extract contains terpemoids, alkaloids and flavonoids. Our results showed that C.nutans in aqueous extract exerted a significant antiproliferative effect on HeLa cells (ICso=13±O.82 pg/mL) and but no ICsowas detected by methanol extract on HeLa cells. No significant activities (IC50 = not detected) were present in vero cells treated with both aqueous and methanol crude extract. Whereas HeLa and Vero cells treated with control drug, tamoxifen shows a significant cytotoxicity effect with IC50 values of 3.8±0.19 pg/mL and 2.2±0.029 pg/mL respectively. Hoechst 33258 stain showed that aqueous extract of C.nutans induce cell death on HeLa cells via apoptosis. The aqueous extract of C.nutans exert the anti-cancer activity against cultured human cervical cancer cell lines with cytoselectivity property and induces cell death by apoptosis pathway , suggesting a promising alternate therapeutic substance for cancer prevention and treatment